PERANCANGAN SISTEM INFORMASI DAN APLIKASI PEMESANAN MAKANAN DI KAFE BERBASIS ANDROID - Anggun Desrivawany; Dedy Irfan; Oktoria Oktoria (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2015)
The advancement of technology specially in mobile sector gives a lot of advantages and facilities in time-saving  and labor-saving. Its scope has already extended to various aspects such as in education, entertainment, up to business sector. Cafe business is increasing in number in Indonesia. Various menu of food becomes the attraction of each cafe compared to food which is served at home. The large number of people visiting cafe demands cafe owners to improve the service so that visitors feel comfortable.  One way to do it is by creating a computerized system. In this case, the service given to customers visiting cafes is still done manually, namely during food-ordering process, waitress note down orders using stationary media. Due to many problems which are caused by manual food-ordering, a solution to overcome the problem is needed. Therefore, an aplication which can help waiters in food-ordering process is required so that it can facilitate customer demand management and time and labor efficiency. Since everything will be organized well, at the end the purpose of the cafe can be achieved. This aplication will facilitate users to input customers’ orders. This food-ordering aplication is designed in the form of mobile-based aplication which is addressed to mobile android operation system. Keywords: information system, application, café, smartphone, Android.